Influence of knowledge intensive business services (KIBS) on firm innovation - Braga, Alexandra Maria da Silva (2017)
The ability to innovate is recognized, internationally, as a key factor of competitiveness in the business world. In the services sector, the rapid growth of knowledge intensive business services (KIBS), has demonstrated that they have a very important role in innovation processes. The scientific community, increasingly, recognizes that service firms innovate alone, but, more importantly, innovation, in this sector, affects all sectors of the economy, due to the transfer of their innovation to other economic activities. The KIBS act as knowledge spreaders, contributing, in different ways, to the process of innovation of related firms: facilitators, carriers and/or sources of innovation. The literature also emphasizes its role as innovation co-producers. In this context, through inter-firm cooperation, it is possible to share and/or create knowledge. This provides a positive output for the firms involved, either in terms of technology, or by creating new products/services. In light with such arguments, approaching the influence of KIBS in firms with regard to innovation seems to be critical to knowledge. In order to achieve this goal, we developed a study mapping scientific publications, intellectual structure and research trends on the intensive business services in knowledge, highlighting the current mainstream approaches on the topic of innovation and knowledge, supported empirically, which identified the relationship between the dimensions that influence the processes of innovation and internationalization in Portuguese KIBS fims. The framework consists of five key dimensions: innovation, knowledge, cooperation, localization and internationalization. A first approach used qualitative data (interviews with KIBS’ CEOs and academic experts). Subsequently two quantitative studies used data gathered through investigation in KIBS firms listed statistics official on R & D in Portugal, produced from the Survey on Scientific and Technological Potential (IPCTN) Firms, yielding a total of 58 responses (approximately a response rate of 15%). To empirically test the research hypotheses, we used univariate and multivariate statistical analysis. The results obtained support the relationships between the selected key dimensions (innovation, knowledge, network, location and internationalisation) — proposed on the literature review. The results show that knowledge personalisation has a positive influence in proactive strategies of internationalization, such as, external innovation and new organizational methods. When KIBS cooperate with clients it has a positive impact in reactive and cost strategies of the internationalization process. Therefore, the results of this study indicate that high levels of cooperation with other firms and universities, urban location and social, institutional and technical knowledge of KIBS, favor both the firms’ innovation and their entry into new foreign markets – internationalisation.